1997
DOI: 10.1037/0735-7044.111.5.1031
|View full text |Cite
|
Sign up to set email alerts
|

Metrifonate improves associative learning and retention in aging rabbits.

Abstract: The cholinergic system is known to show deterioration during aging and Alzheimer's disease (AD). In response, a therapeutic approach to AD has been to attempt to compensate for the decrease in central cholinergic function by potentiating the activity of the remaining intact cholinergic cells with cholinesterase (ChE) inhibitors. In this study treatment with the long-lasting ChE inhibitor metrifonate facilitated acquisition and retention of eyeblink conditioning in aging rabbits. Metrifonate treatment resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 72 publications
3
25
1
Order By: Relevance
“…Specifically, AChE inhibition is greater in aged subjects compared with young subjects, as measured in brain or plasma, when using tacrine, donepezil, or galantamine (Kosasa et al 1999;Woodruff-Pak et al 2001). Second, galantamine produces relatively less AChE inhibition than do other cholinesterase inhibitors (Hallak and Giacobini 1987;Thomsen et al 1991;Kronforst-Collins et al 1997b). It is possible that the level of cholinesterase inhibition produced by galantamine was below a detectable threshold, at the dosage used, for young rabbits, as measured using RBCs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Specifically, AChE inhibition is greater in aged subjects compared with young subjects, as measured in brain or plasma, when using tacrine, donepezil, or galantamine (Kosasa et al 1999;Woodruff-Pak et al 2001). Second, galantamine produces relatively less AChE inhibition than do other cholinesterase inhibitors (Hallak and Giacobini 1987;Thomsen et al 1991;Kronforst-Collins et al 1997b). It is possible that the level of cholinesterase inhibition produced by galantamine was below a detectable threshold, at the dosage used, for young rabbits, as measured using RBCs.…”
Section: Discussionmentioning
confidence: 96%
“…Pretreatment was intended in part to increase the likelihood that any observed benefits afforded by galantamine were attributable to a stable modified biological baseline rather than an initial transient response to the drug. Our previous experience with the cholinesterase inhibitor metrifonate revealed that amelioration of age-related learning deficit was achieved by a steady-state cholinesterase inhibition with pretreatment (Kronforst-Collins et al 1997b).…”
Section: Drug Treatment and Trainingmentioning
confidence: 99%
“…Acquisition of either trace EBC (rats and rabbits) or WMZ (rats) results in a reduction of the post-burst AHP in CA1 pyramidal neurons (Moyer Jr. et al 1996;Oh et al 2003;Kuo et al 2004). In addition, systemic administration of compounds that reduce the AHP result in an enhancement of learning hippocampus-dependent tasks (Kronforst-Collins et al 1997;Weiss et al 2000). Based on these findings, we hypothesized that training rats on two hippocampus-dependent tasks would result in facilitation of the second task.…”
Section: Discussionmentioning
confidence: 99%
“…The long-lasting post-burst AHP is reduced in hippocampal cells from animals that have learned a hippocampus-dependent task (Moyer Jr. et al 1996;Oh et al 2003), and increased in aging animals that have difficulty learning. Pharmacologically reducing the post-burst AHP in vivo with calcium channel blockers (nimodipine) (Deyo et al 1989), acetylcholine agonists (CI-1017) (Weiss et al 2000), or cholinesterase inhibitors (galantamine and metrifonate) (Kronforst-Collins et al 1997;Weible et al 2004) leads to improved learning in aging animals. Thus, the finding that blocking the BK channel results in slowed learning is somewhat surprising, given the previous report of a reduction in the BK-mediated fast AHP after learning tEBC (Matthews et al 2008).…”
mentioning
confidence: 99%